PENGEMBANGAN MEDIA E-COMIC BILINGUAL SUB MATERI SALURAN DAN KELENJAR PENCERNAAN - Savitri, Ely; Panjaitan, Ruqiah Ganda Putri; Titin, Titin (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2016)
Abstract ___________________________________________________________________ This study aims to know the validity of e-comic bilingual as a learning media sub materials digestive tract and gland. The method used in this study is research and development. The subjects in this study are three senior high schools in Pontianak. The instrument used in this study is the form of media validation. The eligibility of e-comic bilingual is measured through validity test by 10 validator consist of 5 material expert validator and 5 media expert validator. The research results showed that e-comic bilingual media of digestive tract and gland is indicated as eligible in order to be used as learning media with an average score of material expert validation at 3.48 and a media expert validation at 3.53.